Social formations of early South India - Gurukkal, Rajan (New Delhi Oxford University Press, 2012)
With reference to Tamil Nadu and Kerala, India.
section 1. Historiography and method -- section 2. Early social formations -- section 3. Social transformations -- section 4. The new social formation.
includes bibliopgraphical references and index
Keywords: Social change -- India -- Tamil Nadu; Social change -- India -- Kerala; Tamil Nadu (India) -- Social conditions; Kerala (India) -- Social conditions